Investigating the link between managers' green knowledge and leadership style, and their firms' environmental performance: The mediation role of green creativity. (19th April 2021) - Riva, Farzana; Magrizos, Solon; Rubel, Mohammad Rabiul Basher
Abstract: Despite extensive literature on green hotel management and sustainability, scant attention has been given on the role of managers to solve environmental related issues. This study's aim is to assess the effects of managers' green knowledge and green transformational leadership on firms' environmental performance with the mediating effect of green creativity. The study analyzes the perceptions of 363 employees in different managerial positions of the hotel industry employing Partial Last Square Structural Equation Modeling. The findings of the study show a positive effect of green knowledge and green transformational leadership on green creativity and green transformational leadership on environmental performance. Furthermore, green creativity is also found to have significant mediating effect between green knowledge and environmental performance, and green transformational leadership and environmental performance relations. The main implication of the current research is that managers' green concerns might help the stakeholders in the hotel industry to respond through appropriate green initiatives for their organizations. Further suggestions for literature and practice are discussed.